Prevalence of serum cobalamin and folate deficiency among children aged 6–59 months: A hospital-based cross-sectional study from Northern India - Surbhi Gupta; Partha Haldar; Archana Singh; Sumit Malhotra; Shashi Kant (Journal of Family Medicine and Primary Care, 2022)
Context: Cobalamin and folate are essential for the synthesis of nucleic acids and in the maintenance of myelin. They are required during the period of the rapid growth of infancy and childhood. Their deficiency may result in nutritional anemia and neurological manifestations. There is paucity of literature regarding the prevalence of cobalamin and folate deficiency among North Indian children aged 6–59 months. Aim: The aim of this study was to estimate the prevalence of serum cobalamin and folate deficiency among children aged 6–59 months, attending a secondary care hospital. Settings and Design: Children were recruited from pediatrics OPD of the sub-district hospital (SDH), Ballabgarh, Haryana, through systematic random sampling. Hemoglobin was measured by an automated analyzer. Serum cobalamin and serum folate were estimated using enhanced chemiluminescence based immunoassay. Results: A total of 420 children were recruited, of which 392 provided a blood specimen. Prevalence of cobalamin, folate deficiency, and anemia were 22.3% (95% CI: 18.3–26.7), 10.9% (95% CI: 8.2–14.6), and 81.9% (95% CI 77.7–85.4), respectively. The proportion of children with cobalamin deficiency who had anemia was 97.7% compared to 95.7% among those with no cobalamin deficiency (P = 0.396). Similarly, the proportion of children with folate deficiency who had anemia was 95.2% compared to 96.2% among those with no folate deficiency (P = 0.765). Conclusion: We found that almost one in five children aged 6–59 were deficient in cobalamin, and one in ten were deficient in folate.